Effects of biomass pellet composition on the thermal and emissions performances of a TLUD cooking stove - Zongxi, Zhang; Zhenfeng, Sun; Yinghua, Zhang; Hongyan, Ding; Yuguang, Zhou; Yixiang, Zhang; Ahmad, Riaz; Pemberton-Pigott, Crispin; Renjie, Dong (International Journal of Agricultural and Biological Engineering, 2017)
Indoor air pollution is ranked the 5th in the Global Burden of Disease index of the World Health Organization (WHO). Almost half of the world’s population depends on biomass fuels to meet their basic energy requirements for cooking, lighting and space heating. When fuel is badly combusted in poorly designed stoves, the fuel-stove combination results in high level of noxious emissions entering the home, accumulating to dangerous levels. In this study, a Chinese unvented top lit updraft (TLUD) biomass stove was operated with three different biomass pellets formed from corn stover, cotton stalk and peanut shells. The performance tests were conducted according to the latest standard from the Chinese Ministry of Agriculture. The calorific value, moisture level, volatile matter and elemental composition are reported for each. The thermal efficiencies of the stove were 15.3%, 10.1% and 14.4%, respectively. The cooking powers were 2.68 kW, 1.61 kW and 1.57 kW. The exhaust was collected using a hood and tunnel. The CO, NO and NOX were drawn after passing 1.5 m along the tunnel and the Particulate Matter (PM) was sampled after 1.6 m. The Emission Factors (EF) for CO, NO, NOX and PM10 are reported on both a mass per unit energy delivered to the pot (g/MJNET) and a mass per mass of fuel basis (g/kg). The range for CO was 4.56-7.61 g/MJNET (11.25-21.25 g/kg); NO was 0.75-1.23 g/MJNET (2.09-3.04 g/kg); NOx was 1.13-1.90 g/MJNET (3.14-4.86 g/kg); PM10 was 0.59-0.85 g/MJNET (1.67-2.09 g/kg). The range in these values was more significantly influenced by the fuel moisture content and the percentage of volatile matter than by variations in the elemental composition.Keywords: indoor air pollution, biomass stove, pellets, thermal performance, emissionsDOI: 10.25165/j.ijabe.20171004.2963Citation: Zhang Z X, Sun Z F, Zhang Y H, Ding H Y, Zhou Y G, Zhang Y X, et al. Effects of biomass pellet composition on the thermal and emissions performances of a TLUD cooking stove. Int J Agric & Biol Eng, 2017; 10(4): 189–197.